Representations of the First Colonial “Civil War” in Victoria’s Reign: the Canadian Rebellions in the English Press (1837–1838) - Françoise Lejeune (Cahiers Victoriens et Edouardiens)
This article examines the various representations circulating in the British press of an unexpected and peculiar occurrence: a “civil war” which took place in the white colonies of Canada in 1837–38. In fact, the terms used to refer to the event varied according to the sources. English leaders and editorials reported on a “civil war” in the colonies, while American newspapers whose despatches were quoted verbatim in the English press, more often referred to “rebellions” or “insurrections”. By reflecting on such a discrepancy in the representations of this colonial crisis, we might wonder why what seemed to clearly have been short-lived insurrections rapidly controlled by the British army, were represented under the alarming colours of “civil war” in England, in the press and in official despatches. Combined to the frightful news from Canada, Victorian fears of the civil war were also heightened in 1837, by the representations of civil wars and revolution published by Edward Gibbon and Thomas Carlyle whose histories of the decline of the Roman Empire and the French revolution. The Canadian “civil war” was described as a threat to the harmonious working of the British parliamentary monarchy at home and in the Empire. It led the press, moderate and radical, to reassess the values of the “English” Constitution and the capacity of British colonists as well as “the mob” to work with it, at a timely period: the beginning of Victoria’s reign and that of her second Empire.